INFEKSI NEMATODE USUS PADA SISWA SEKOLAH DASAR NEGERI (SDN) KARANG MULYO 02, KECAMATAN PEGANDON, KABUPATEN KENDAL - Maharani I.P, Astri (Lembaga Penelitian Universitas YARSI, 2005)
The intestinal helminth infection was suffered mostly by pre-elementary and elementary students. This work was conducted to study the relationship between hygiene sanitation and intestinal helminth infection and the relationship between intestinal helminth infection and nutrition status in the students of SDN Karang Mulyo 02, Pegandon District, Kendal Regency. Survey method with a cross sectional approach was used in this study. The result showed that 21,57% of 51 subjects suffered intestinal helminth infection and the most common infection was a combination of Necator americanus and Ancylostoma duodenale infection. Hygiene sanitation of 74,51% respondens was good, however the nutrition status of the students was mostly bad according to weight to age as well as height to age, indicates i.e 56,87% out of 51 respondens. The energy and protein levels were less than standard and employing chi square analysis a positive correlation was found between hygiene sanitation and intestinal helminth infection but a negative correlation was found between intestinal helminth infection and nutrition status